STRATEGI RESOLUSI KONFLIK TENURIAL PADA PBPH PT. WANA SUBUR PERSADA - Rachmad, Harul Mardin; Hardiansyah, Gusti; Rifanjani, Slamet; Roslinda, Emi; Diba, Farah (Universitas Tanjungpura, 2025)
This research mapped tenure issues in PBPH PT Wana Subur Persada (WSP) and explored the appropriate strategies and approaches used by PBPH PT WSP in handling tenure conflicts in its area. Researchers analysed the actors involved in this tenure conflict issue using the Rapid Land-Tenure Assessment (RaTA) and Dispute Style Analysis (AGATA) tools with The Thomas Kilmann Instrument. The Kilmann Instrument shows that the disputing style of Karang Betung Village - Kenyabur Village and Teluk Kebau Village - Merabu Jaya Village is Agitation, Tembesuk Village - PT WSP is Compromise and Nanga Engkulun Village - PT WSP is Collaboration. The conflict resolution strategy carried out by PBPH PT WSP in its working area in addition to mediation in positive law and customary law is also carried out by maximising the Corporate Social Responsibility (CSR) program. Community welfare improvement programmes carried out include forestry partnerships, agroforestry development, development of non-timber forest products (NTFPs) and livestock cultivation assistance. So that the community has an income to support the economy while waiting for the results of the HTI land that is cooperated.Keywords: conflict, dispute style analysis, Forest Utilization License, Rapid Land-Tenure Assessment, tenure.AbstrakPenelitian ini memetakan permasalahan tenurial pada PBPH PT. Wana Subur Persada (WSP) serta menggali strategi dan pendekatan yang tepat yang dipakai PBPH PT. WSP dalam penanganan konflik tenurial di wilayahnya. Peneliti menganalisis aktor yang terlibat dalam permasalahan konflik tenurial ini menggunakan alat penilaian Rapid Land-Tenure Assessment (RaTA) dan Analisis Gaya Bersengketa (AGATA) dengan The Thomas Kilmann Instrument. Instrumen Kilmann menunjukkan bahwa gaya bersengketa Desa Karang Betung - Desa Kenyabur dan Desa Teluk Kebau